CuNb2O6 Particles Obtained via Solid-State Reaction and Application as Electrocatalyst for Oxygen Evolution Reaction - Kívia F. G. de Araújo; Cleber S. Lourenço; Vitor M. S. F. Souza; Matheus D. da Silva; Gabriel D. S. Vasconcelos; Maria J. S. Lima; Jakeline R. D. Santos; Kelly C. Gomes; Francisco J. A. Loureiro; Marco A. Morales; Uílame U. Gomes (Ceramics)
Copper niobate (CuNb2O6) is an important compound due to its low cost and polymorphism, presenting monoclinic and orthorhombic phases, which leads to unique physical–chemical properties. The electrochemical performance of efficient electrocatalysts for the oxygen evolution reaction (OER) is of importance in order to produce hydrogen gas from water. In this context, this work reports the synthesis of CuNb2O6 particles by high-energy milling for 5 and 10 h, and subsequent thermal treatment at 900 °C for 3 h. The samples were characterized by XRD, XRF, FESEM, RAMAN, UV–Vis, and FT-IR techniques, and were applied as electrocatalysts for the OER. The samples had both monoclinic and orthorhombic crystalline phases. The band gaps were in the range of 1.92 to 2.06 eV. In the application for the OER, the particles obtained by 5 and 10 h of milling exhibited overpotentials of 476 and 347 mV vs. RHE at 10 mA cm−2, respectively. In chronopotentiometry experiments for 15 h, the samples exhibited excellent chemical stability. The electrochemical performance of the sample milled for 10 h showed superior performance (347 mV vs. RHE) when compared with electrocatalysts of the same type, demonstrating that the methodology used to synthesize the samples is promising for energy applications.